18th Nordic Geotechnical Meeting NGM2020 Urban Geotechnics Preface. Issue 1 (April 2021) - Unknown
Abstract : The 18th Nordic Geotechnical Meeting NGM 2020 was arranged as a virtual conference on 18 th -19 th January 2021. The conference was organized by Finnish Geotechnical Society and Finnish Association of Civil Engineers, both from Helsinki. The Nordic Geotechnical Meetings are the oldest regional geotechnical conference series starting from Stockholm since 1950. As the name suggests this event is rather a more informal meeting than an actual formal conference even though normal conference content is followed. The 18 th Nordic Geotechnical Meeting, originally scheduled to take place in Helsinki in May 2020, had to be postponed due to COVID-19 pandemic. The pandemic and travel restrictions were the reason to organize a virtual conference on 18 th -19 th January 2021, arranged in parallel with the 14 th Baltic Sea Region Geotechnical Conference. The 18 th NGM attracted total of 271 participants from 32 countries, successfully allowing to share insights and discuss ideas related to Urban Geotechnics, the main topic of the meeting. The 18 th NGM proceedings contain 78 scientific papers presented during the conference alongside 16 industry presentations. In the proceedings, the papers are divided into sections related to: Case histories Soil and rock investigations (incl. geophysical methods) Slope stability and other geohazards Climate change and circular economy Eurocode and standardization Modelling, monitoring and digital solutions Ground improvement methods Foundations and deep excavations Transport infrastructure Statistical methods, risk analysis and reliability-based design Cold regions – frost. Furthermore, three keynote speakers presented during the 18 th NGM. The signature keynote entitled "From soft soil modelling to engineering application" was given by Professor Minna Karstunen from the Chalmers University of Technology. The other two keynotes were awarded jointly with 14 th BSGC: Professor Masaki Kitazume "Applications of deep mixing technology for mitigating earthquake disaster in Urban Area" from Tokyo Institute of Technology, Japan, and professor Jean-Sebastien L'Heureux "On the use of benchmark test sites for research and development in geotechnical engineering" from the Norwegian University of science and technology. The conference had 66 oral presentations and 26 on-demand prerecorded presentations. For both conferences, four parallel streams were created. The conference platform used was ExOrdo. After each presentation there was about five minutes possibility to ask questions. Also chat possibility was available during presentations. The conference platform has been open for two months after the conference. The audience has been given possibility to continue discussion during these two months through the ExOrdo platform. Organizers asked participants to fill a feedback survey and the conference was considered successful as the participants gave 3.9 for overall conference experience and 3.8 for the virtual platform of the event (scale 1 poor … 5 excellent). We wish to express our thanks to all the authors and keynote speakers for their valuable contribution to the success of the conference. We want also to thank our sponsors, session chairs, stage managers, members of scientific board and organization committee, without whom this event would not be possible. Leena Korkiala-Tanttu NGM 2020 scientific board chair, Editor Anne Tuomela and Anssi Rauhala Co-editors